Geology & Geomechanics of Rhyolite, Lanchang, Pahang - Ooi, Wei Chian (Universiti Teknologi PETRONAS, 2016)
Limited geological and geomechanical studies have been done on the rhyolite of the Lanchang area, Pahang. Hence, this study aims to investigate the general geology and geomechanical characterization of the rhyolite outcrop which is located at Maha Mayang Quarry, Lanchang. The geology of this outcrop consisted of 2 type of lithologies, which are light-colored rhyolite (Sample 1) and reddish igneous rock (Sample 2). The area is subjected to compressional stress in North-South direction as the outcrop is highly fractured. XRF analysis results show that Sample 1 has 64.9% silica content, representing rhyolite while Sample 2 has low silica content (49.2%) and high iron composition (19%) which indicates mafic rock. Hornblende also occurs in the mafic igneous rock. The geomechanical analysis such as Triaxial test, Brazilian Test, Schmidt Hammer and Point Load Test show both samples are very strong rocks with result of high value obtained, characterizing as R5 grade. With the results, Sample 1 and Sample 2 have the characteristic of being competent igneous rock. Moreover, from discontinuity survey, the determination of the basic Rock Mass Rating, RMRbasic for both rock samples are 84, classifying as very good rock.